The Communication Network in Community-Based Solid Waste Management (Waste-Bank) In Makassar, Indonesia - Wellang, MA; T Matsumoto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
The Waste Banks initiative, which has been in operation in Makassar City since 2013, attempts to alleviate Indonesia's waste problem by encouraging community participation in garbage separation within the framework of community-based waste management (CBWM). Despite its extensive history, no significant progress has been made. This study dives into the communication network of waste bank players in Makassar City, concentrating on the three best performance Waste Banks. Data gathering included interviews and questionnaires with each participant, and communication networks and sociograms were analyzed using Social Network analytic (SNA) and the UCINET 6 analytic tool. The major findings reveal a startlingly low network density of 1% in each waste bank (Lamber Borong: 0.063, Sayang Rennu: 0.032, Sayang Rennu: 0.032). Members' low level of active communication is shown. Furthermore, each waste bank identifies a member with the highest degree of centrality, detailing communication pathways and emphasizing that single person's importance. In contrast, an individual with the lowest closeness centrality score in each waste bank displays their capacity to efficiently disseminate information throughout the network. Furthermore, several people in each waste bank have a high betweenness centrality score, highlighting their vital role in linking others inside the trash bank network.